Effect of High Fructose Corn Syrup and Citric Acid in Broiler Diets on Performance, Gut pH, Immunity, Antioxidant Status and Some Blood Parameters - Gökhan Şen; Ali Karapinar; Mehmet Naci Oktay; Miyase Çinar; Mehmet Başalan (Veterinary Medicine and Science)
ABSTRACT The objective of this study was to determine the effect of high fructose corn syrup (HFCS) and citric acid (CA) in broiler diets on performance, gut pH, immunity, antioxidant status and some blood parameters. A total of 120 Ross 308 chicks at the age of 0 days were divided into 4 groups with 3 subgroups of 10 chicks each: control (CON), 50 mg/kg HFCS, 30 mg/kg CA and 50 mg/kg HFCS + 30 mg/kg CA (HFCS + CA). It was determined that body weight gain (BWG) was highest in the CA group and was similar to the CON group, whereas it was lower in the HFCS + CA group than other groups (p < 0.05). The feed conversion rates of the CA and the CON groups were similar and lower than the others (p < 0.05). Carcass weights and ratios increased in the CA group (p < 0.05). There were significant differences between the weights of liver and pancreas of groups (p < 0.05). Serum high‐density lipoprotein (HDL)‐CHO and GLU levels increased in the HFCS + CA group (p < 0.05). Serum total cholesterol (TCHO) level in the HFCS group was similar to the CON group and lower than the other groups (p < 0.05). Serum tumour necrosis factor‐α (TNF‐α) and interleukin‐1β (IL‐1β) values were determined to be highest in the HFCS group and different from the CON group (p < 0.05). It was observed that HFCS negatively affected performance, whereas CA positively affected. HFCS + CA increased serum TCHO and HDL‐CHO levels and CA led to an increasing trend in total antioxidant status (TAS) level. Although HFCS had a positive effect on TNF‐α and IL‐1β, similar of immunoglobulin G (IgG) and immunoglobulin M (IgM) levels between groups was observed.